Meningkatkan Motivasi Belajar PAHBP Materi Ajaran Avatara dan Deva Melalui Model Pembelajaran Project Based Learning di Kelas VII SMP Negeri 2 Arut Selatan Kabupaten Kotawaringin Barat Semester 1 Tahun Pelajaran 2019/2020 - Wayan Sweda (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The low learning motivation of students is very influential on the acquisition of student achievement, especially in the matter of Avatara and deva teachings. This is evidenced by the acquisition of pre-test results for Avatara and deva teachings from 6 seventh-grade students of SMP Negeri 2 Arut Selatan. Seeing the statement above, the author is interested in researching and testing the extent to which the motivation to learn PAHBP in avatara and deva material is through a project-based learning model. This research method uses classroom action research. The research was carried out at SMP Negeri 2 Arut Selatan Class VII. The research was carried out from August 2019 to October 2019. The research subjects were Class VII students of SMP Negeri 2 Arut Selatan. Data collection techniques in this research are observation, interview, and documentation techniques. The results of the evaluation of the second cycle are known that classical learning completeness reaches (100%) with the average final score of students reaching (84.8) which previously in the pre-cycle classical learning mastery was known to reach (33.33%) with an average final test score students reached (65.95) and in the first cycle of classical learning completeness reached (75%) with an average final test score of students (74.2). From this information, it can be said that the project-based learning model can be applied to the Avatara and deva teaching materials and can increase learning motivation in Class VII semester I SMP Negeri 2 Arut Selatan.